Les Poupees de Paris (Plastichrome of Texas, Inc.)
Les Poupees de Paris in the Lido Theater at HemisFair '68. A marionette show for adults only with much of the flavor of the famed Folies Bergere in Paris. Created by Sid and Marty Krofft, this show features over 200 wooden wonders.